Age estimation of a skeletonized human remains using the mann and lamendin methods: a case report - Sandi, Indah Maydila; Safitry, Oktavinda; Suhartono, Antonius Winoto; Pattihahuan, Ira Zefanya; Auerkari, Elza Ibrahim (Padjadjaran Journal of Dentistry, 2025)
Introduction: An autopsy examines a deceased body to determine the cause of death. Forensic science applies scientific methods to aid law enforcement. After death, the body progresses through five decomposition stages: fresh, bloated, active decay, advanced decay, and skeletal, each providing crucial information for investigations. This case report purpose is to described age estimation of a skeletonized human remains using the mann and lamendin methods. Case Report: The body was in the skeletonization phase with partial soft tissue remaining on various body parts. No signs of trauma or bleeding were found on the bones. A total of 22 teeth were present, and three teeth were missing post-mortem. The biological age of the individual was estimated using Mann's method, which calculates age based on the palatal suture, followed by Lamendin's method, which uses the periodontosis, root height, and the transparency of the teet Conclusion: The estimation of the individual was more than 50 years using Mann’s method, and between 64 to 70 years using Lamendin’s method. This case demonstrates that forensic odontology provides  a non-invasive, cost-effective, and accurate approach for determining the age of a skeletonized remains by analyzing the sutura palatina and teeth.